(untitled) (Boston, 1988)
"The Writer's Handbook " is an indispensible companion for everyone in the writing profession. Packed with provocative articles, useful advice, key contacts, hints and discussion, this practical and straightforward guide provides full details on the key markets.
Keywords: English language,Tiếng Anh; Rhetoric,Tu từ học